Class Dynamics of Consumerism: A Sociological Analysis of Consumption Patterns in Kathmandu - Shrestha, Bimal Babu (Journal of Rapti Babai Campus, 2026)
This study explores the patterns of consumer behavior across various social groups. It is based on how class disparities and hierarchies are created. Furthermore, it explores on how class identity is formed in Kathmandu Metropolitan. In the contemporary society, the study aims to know about the intersection of consumer behavior, class identity, and social hierarchies. It focuses on how consumption patterns are shaped by economic constraints, desire for social mobility, and social pressures. The qualitative in – depth interview method was used on twenty respondents altogether. Respondents were selected purposively from various social class, and using unstructured interview schedule for more than six months. The key findings reveal a distinction between inspirational consumption and instinctive consumption. Precisely, the findings reveal consumption driven by wish to project a higher status and consumption driven by immediate practical needs. The research highlights how economic factors influence consumption, with lower-income individuals. How economic factors influence consumption with lower – income individuals focusing on essentials was highlighted. Similarly, how higher – income groups indulge in non – essential purchases, and reinforce class divisions. E-commerce and social media play significant role to shape consumption behavior. It is due to these digital platforms. It provides access to goods and services. Furthermore, it creates new forms of social validation through trends and influencer endorsements. The study further examines about the impact of social perceptions on class identity as middle – class individuals strive to emulate upper – class ideals despite financial strain. Conveniences over cost has increased the digital consumption. It further underscores the evolving nature of consumer behavior in urban environment. Lastly, the research highlights the tension between social aspirations and economic realities and underscores the role of consumption to determine the social hierarchies.